Rethinking Development Challenges for Public Policy
XVIII, 297 p.
Keywords: Covers topical issues for Africa's development, economics and politics of climate change, water management, public service delivery, and delivering aid. The authors argue that these issues should be included in the post-MDG paradigm and add an important voice to recent moves by academics and practitioners to engage with each other.